The effect of defaunatıon on volatile fatty acids in akkaraman lambs - Mehmet Kocabatmaz; M. Yaşar Aksoylar; Zafer Durgun; Mursayettin Eksen (Eurasian Journal of Veterinary Sciences)
Two groups of Akkaraman lambs (faunated and defa-unated lambs) were used to investigate the effect of the presence or absence of rumen ciliate protozoa on pH, volatile fatty acids of rumen content and weight gain.